The Incidence and Risk Factors of Surgical Site Infection Following Cesarean Section - Hind Ghannam Alruwaili; Wedad M. Almutairi; Areej A. Abunar (Nursing Research and Practice)
Sample: A convenience sample of 124 mothers within 30 days after CS was used; data were collected from July 2021 to August 2021. This study found that the incidence of SSI after CS was 4% of the mothers who underwent CS operations in the Maternity and Children Hospital in Sakaka. Besides, the results showed that there is a significant association between the type of anesthesia (spinal) and SSI following CS (Chi = 4.288, p≤0.05). To conclude that the incidence of SSI following CS was 4%, comparable to the international rate, and spinal anesthesia was the confirmed risk factor in our sample. Further studies should be carried out with larger samples and in more than one hospital in Sakaka, Saudi Arabia.